2023
DOI: 10.1186/s40246-023-00480-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of a novel super-enhancer-associated lncRNA prognostic signature and identifying LINC00945 in aggravating glioma progression

Abstract: Background Super-enhancers (SEs), driving high-level expression of genes with tumor-promoting functions, have been investigated recently. However, the roles of super-enhancer-associated lncRNAs (SE-lncRNAs) in tumors remain undetermined, especially in gliomas. We here established a SE-lncRNAs expression-based prognostic signature to choose the effective treatment of glioma and identify a novel therapeutic target. Methods Combined analysis of RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Overexpression of LINC00945 promoted proliferation, EMT, migration, and invasion of glioma cells. Mechanistically, BRD4 mediated epigenetic activation of LINC00945 [ 44 ]. The study constructed the prognostic SE-lncRNA signature and provided a potential therapeutic target for glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LINC00945 promoted proliferation, EMT, migration, and invasion of glioma cells. Mechanistically, BRD4 mediated epigenetic activation of LINC00945 [ 44 ]. The study constructed the prognostic SE-lncRNA signature and provided a potential therapeutic target for glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the significant regulatory role of lncRNA in gliomas, offering potential breakthroughs in the clinical diagnosis and treatment of gliomas [6,7]. At present, types, numbers and functions of lncRNA are not clear.…”
Section: Introductionmentioning
confidence: 99%